ANALYSIS OF REALIZED ACTIVITIES OF THE TOURIST COMMUNITY OF SARAJEVO CANTON AND THEIR PRESENTATION THROUGH THE WEBSITE AND SOCIAL NETWORKS FOR THE PROMOTION OF SPORTS TOURISM AND TOURISM - Amer Hodžić; Tarik Huremović; Dževad Džibrić (Sport Scientific And Practical Aspects, 2025)
Tourist boards, through their social activities, can make a tourist destination, tourist attractions and tourist products attractive, unique, and special. Through relevant scientific knowledge, using the tools and techniques of destination management as well as modern forms of communication, tourist boards can make the entire area of a tourist destinationvery interesting and desirable for tourist visits throughout the year by promoting the specificity, authenticity and originality of the tourist offer and tourist products.